Intermodal criteria to include non-motorized transport modes in the influence zone of Integral System of Transport of metropolitan area of San Salvador (TRIM. Tordesillas, revista de investigación multidisciplinar, 2020)
The principal aim of this paper is to understand the socials and technical dynamics that prevent intermodal mobility. From that knowledge, establish criteria that allow intermodal mobility in AMSS, mainly guided by the Amar (2011) ideas of values the richness of the opportunities of the meetings, the experience of those encounters, the activities and breaks provided by those trips that favor conditions of bond or "religancia". The methodological structure link three research technics that consider the nature of determinant aspects of the problem, finally it establishes preliminary results that contribute to define intermodal design criteria.
Keywords: intermodal criteria; urban mobility; intermodal systems; transport; mobility; networks